Punca Dan Kesan Media Berunsur Agresif Terhadap Tingkah Laku Remaja Di Johor Bahru - Halimah Ma’alip; Azizi Yahaya; Nordin Ajmain; Pg. Razmahayati Pg. Hj. Mahmud; Ronnel (Southeast Asia Psychology Journal, 2022)
This study aims to examine the causes and effects of aggressive media on adolescent behavior. The respondents are adolescent who are also a high school students in Johor Bahru. A total of 227 respondents consisting of 158 males and 69 females were involved in this study. A set of research instruments in the form of a questionnaire was used for the purpose of data collection. Part A is the demographic part. While part B, it is to explain the research objectives and to test the hypothesis. Questionnaire items in Part B are measured using a five-point Likert scale. The data obtained was processed using the Statistical Package for Social Science, Version 26.0 (SPSS) for descriptive and inferential analysis. A pilot study was conducted to measure the reliability of the questionnaire. The findings show that online games are the most dominant influence toeards the aggressive behavior of teenagers in Johor Bahru with a mean of 4.20. The findings also show that the effect of aggressive media, the reasons for watching aggressive, and the form of media programs are not a good predictor of adolescent aggressive behavior because only contribute 15%. This study has implications on the role of media that are to re-evaluate the broadcast programs to minimize aggression and violence elements that can cause adolescent aggressive behavior.